Geometry in Exposing False Statements - Kuzembaev, Serik; Tuleuova, Gulmarzhan (Рroblems of engineering and professional education, 2022)
At present, for some reason, the number of supporters of the flat Earth hypothesis is growing all over the world. In particular, to confirm this hypothesis, a number of experiments were carried out using the most modern instruments and qualified specialists. This paper discusses the results of these studies and analyzes the methodology for their implementation. Based on the dialectical approach, the inconsistency of the above arguments is shown. One of the main arguments given to prove the flatness of the Earth is the fact that the water surface is horizontal in inland water bodies - lakes and reservoirs. We have explained the mechanism of this phenomenon from the geometrical and hydrostatic points of view. A hypothesis was put forward about the influence of this mechanism on the ocean expanses. An example of ships drifting beyond the horizon is considered. The experience of measuring geodesic curves with the help of high-rise buildings is subjected to a detailed analysis. The tool base is carefully designed and implemented. The conclusions based on the obtained results do not withstand scientific criticism. The unreliability of interpretations in the analyzed works is explained by the imperfection of the research methodology.